2019
DOI: 10.1111/1462-2920.14532
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and distribution of the bmp gene cluster and its Polybrominated products in the genus Pseudoalteromonas

Abstract: Summary The production of pentabromopseudilin and related brominated compounds by Pseudoalteromonas spp. has recently been linked to the bmp biosynthetic gene cluster. This study explored the distribution and evolutionary history of this gene cluster in the genus Pseudoalteromonas. A phylogeny of the genus revealed numerous clades that do not contain type strains, suggesting considerable species level diversity has yet to be described. Comparative genomics revealed four distinct versions of the gene cluster di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 39 publications
3
26
0
Order By: Relevance
“…A previous work has demonstrated that some P . luteoviolacea strains possess the biosynthesis genes and the ability to produce brominated natural products (Busch et al ., 2019). However, a similar survey has not yet been performed for genes encoding MACs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous work has demonstrated that some P . luteoviolacea strains possess the biosynthesis genes and the ability to produce brominated natural products (Busch et al ., 2019). However, a similar survey has not yet been performed for genes encoding MACs.…”
Section: Resultsmentioning
confidence: 99%
“…luteoviolacea phylogeny using 71 bacterial ribosomal genes (Eren et al ., 2015; Delmont and Eren, 2018; Lee, 2019). As observed previously (Vynne et al ., 2012; Busch et al ., 2019), P . luteoviolacea strains fall within one of two major clades (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Busch et al . (2019) proposed vertical inheritance of the bmp biosynthetic gene cluster, which encodes the antibiotic pentabromopseudilin and related brominated natural products in marine Pseudoalteromonas lineages. Brominated compounds from Pseudoalteromonas play a role in larval attachment and metamorphosis in many coral species (Tebben et al .…”
Section: Secondary Metabolites From Cabmentioning
confidence: 99%
“…Sponge chemical ecology 5 (Agarwal et al 2017). The discovery of the hs_bmp gene cluster responsible for the production of PBDEs in H. spongeliae was facilitated by the prior discovery of the homologous bmp gene cluster in marine proteobacteria that encodes biosynthetic enzymes for the elaboration of numerous brominated phenols and pyrroles (Agarwal et al 2014(Agarwal et al , 2017El Gamal et al 2016;Busch et al 2019). Hybridization of fluorescent nucleotide probes revealed that cyanobacterial symbionts are also responsible for the biosynthesis of chlorinated peptidic natural products such as dysidinin in Dysideidae sponges (Flatt et al 2005).…”
Section: Microbial Biosynthesis Of Sponge-derived Natural Productsmentioning
confidence: 99%